2021
DOI: 10.3389/fvets.2020.617647
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Allogeneic Mesenchymal Stromal Cells and the Recipient Immune System: A Comparative Review With Relevance to Equine Outcomes

Abstract: Despite significant immunosuppressive activity, allogeneic mesenchymal stromal cells (MSCs) carry an inherent risk of immune rejection when transferred into a recipient. In naïve recipients, this immune response is initially driven by the innate immune system, an immediate reaction to the foreign cells, and later, the adaptive immune system, a delayed response that causes cell death due to recognition of specific alloantigens by host cells and antibodies. This review describes the actions of MSCs to both suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…Kamm et al (2021) concluded that based on the evidence to date, tendons appear to have improved healing when treated with allogeneic MSCs, and the use of these treatments in equine tendon and ligament lesions is warranted [ 86 ]. Colbath et al (2020) claimed that some of the advantages of using allogenic stem cells include the ability to bank cells and to also reduce the treatment time, to collect MSCs from younger donor animals, and the ability to manipulate banked cells prior to administration [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kamm et al (2021) concluded that based on the evidence to date, tendons appear to have improved healing when treated with allogeneic MSCs, and the use of these treatments in equine tendon and ligament lesions is warranted [ 86 ]. Colbath et al (2020) claimed that some of the advantages of using allogenic stem cells include the ability to bank cells and to also reduce the treatment time, to collect MSCs from younger donor animals, and the ability to manipulate banked cells prior to administration [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory actions of MSCs are closely related not only with their therapeutic mechanisms but also with their ability to evade the immune system, in which the expression of immunogenic molecules also plays a role. Expression of MHC-I by MSCs may result in their immune recognition and elimination since cytotoxic T cells attack foreign cells bearing MHC-I receptors that are bound to an alloantigen ( 44 ). On the other hand, natural killer (NK) cells can attack cells lacking MHC-I on their surface ( 45 ), so the expression of MHC-I, although weak, protects MSCs from NK cell-mediated elimination ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in clinical studies, the allogeneic use of MSCs has been described for single ( 12 , 23 , 46 ) and repeated ( 24 , 25 ) treatment of horses suffering from tendon injuries without evidence of any local immunological reactions (absence of heat, swelling, pain or lameness) after intralesional injection. On the other hand, a higher number of circulating CD8 T-cells after repeated intravenous injection of equine allogeneic MSCs has been reported ( 56 , 57 ). The authors suggested this could be an alloantigen-directed cytotoxic response.…”
Section: Discussionmentioning
confidence: 99%